The Potential Roles of Gut Microbiome in Modulating the Immune Response of Asian Redtail Catfish (Hemibagrus nemurus) Vaccinated with Aeromonas hydrophila - Septyan Andriyanto; Yani Aryati; Tuti Sumiati; Angela Mariana Lusiastuti; Nurhidayat; Kurniawan Kurniawan; Rofingah Kuswatun; Nining Nuraeni (Bogor Agricultural University, Indonesia, 2022)
The research aims are to observe the effect of vaccination in microbial profiles and gut microbiome composition. The treatments were as follows: the fishes were injected with PBS and challenged (A); the fishes were injected with freeze–dried vaccine dissolved in 100 ml 0.85% NaCl and challenged (B); the fishes were injected with freeze–dried vaccine dissolved in 50 ml 0.85% NaCl and challenged (C), and the fishes were injected with liquid vaccine and challenged (D). Microbiome composition measurements were carried out on the 21st–day post–vaccination and the 7th day after the challenge test. Fish intestine samples from three replications were tested by Next Generation Sequencing (NGS). Two significant phyla were identified from all treatments, namely Proteobacteria and Firmicutes. Cetobacterium, Candidatus Bacilloplasma, and Clostridium sensu stricto were the genera classified as good bacteria in vaccinated fish. It can be concluded that vaccination can increase the diversity of the gut microbiome, especially bacteria beneficial to the fish host. Chitosan as a coating antigen in freeze–dried vaccine increases gut microbiome's number and diversity better than a liquid vaccine.